THE CONTRIBUTION OF THE BUDDHIST PHILOSOPHICAL CONCEPTS, INCLUDED IN EXEGETICAL BOOKS TO SOLVE PROBLEMS - Sudhammika, N. A. (The Library, University of Kelaniya, Sri Lanka., 2025)
The present study, titled "The Contribution of Buddhist Philosophical Concepts to Solving Psychological Problems: As Included in Sinhala Exegetical Books," was carried out within the broader framework of interrelated key Buddhist philosophical concepts. The research primarily sought to examine whether Buddhist philosophical ideas can be effectively applied to address problems. The main objective was to critically evaluate the applicability of these concepts, as represented in Sinhala exegetical literature, in resolving human problems. Additional objectives included determining whether the term Bosath (intelligent being), along with related philosophical notions, could be applied to individuals engaged in inner development according to the Doctrine, with the goal of achieving personal liberation and assisting others in transcending the karmic cycle (samsara). The study also aimed to identify how these concepts contribute to the realization of the Dhamma and the cultivation of virtuous personal qualities. Furthermore, the research explored the potential of these philosophical concepts to mitigate social and psychological challenges and foster the development of a virtuous society. The significance of the Bodhisattva concept in the context of spiritual advancement was also examined. The hypothesis proposed that the concepts of Buddha, Bodhi, and Bosath are deeply interconnected with other Buddhist philosophical principles. The guiding research questions focused on defining Buddhist concepts, understanding the nature of problems, examining the application of Buddhist concepts in selected exegetical texts, and assessing their practical relevance in problem-solving, especially within the Mahayana philosophical framework. The scope of the study was confined to four Sinhala exegetical texts—Dhampiya Atuva Gatapadaya, Dharmapradipikawa, Pujawaliya, and Visuddhimarga Sannaya and three interrelated concepts: Buddha, Bodhi, and Bosath. Based on a qualitative methodology involving textual analysis and literature review, the findings indicate that a Buddhist-based model of problem-solving can be formulated through critical examination, clarification, and interpretation of the selected sources.
Keywords: Exegetical literature; Problem solving; Philosophical concepts; Buddhism; Righteous